1992
DOI: 10.1007/bf01957748
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal endoscopy in Henoch-Schönlein purpura

Abstract: Gastrointestinal (GI) endoscopy was performed in seven patients with Henoch-Schönlein purpura (HSP). In two patients there were no cutaneous lesions at the time of endoscopy, but inflammation of the duodenum, especially of the second part, led to suspicion of the disease. Upper GI endoscopy showed abnormalities in six of seven cases, and sigmoidoscopy in one of four cases. The changes were more marked in the second part of the duodenum rather than in the bulb or the stomach. The endoscopic findings included re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 11 publications
(10 reference statements)
1
30
0
Order By: Relevance
“…In the present study, however, vasculitis in the mucosa was not shown in any patient. Several studies reported that intestinal IgA deposition in HSP is not always accompanied by vasculitis (4)(5)(6). It remains poorly understood how deposited IgA or IgA immune complexes link to the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, however, vasculitis in the mucosa was not shown in any patient. Several studies reported that intestinal IgA deposition in HSP is not always accompanied by vasculitis (4)(5)(6). It remains poorly understood how deposited IgA or IgA immune complexes link to the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…Staining with hematoxylin and eosin was routinely done for light microscopic observation. IgA was examined using the avidin-biotin-complex method (5,6). In two nonrash patients (Patients 4 and 7) and two HSP patients (Patients 11 and 12), biopsy specimens were also fixed in 4% periodatelysine-paraformaldehyde and were studied for immunoreactivities of IgA1 and IgA2, J chain, and secretory component using the indirect immunoperoxidase method (12).…”
mentioning
confidence: 99%
“…Vasculitis may be found in the submucosal vessels of the intestine [116] although biopsy of this area risks the possibility of perforation in a disease prone to this complication. The findings in superficial biopsies range from nonspecific inflammation to ulceration, edema, hemorrhage, and vascular congestion, presumably due to vasculitis-induced mucosal ischemia [117]. In one study, LCV was found in those ulcerating lesions that were accompanied by hematoma-like protrusions [65].…”
Section: Diagnosis Of Gi Diseasesmentioning
confidence: 98%
“…Kato et al [3] reported endoscopically detected duodenal abnormalities in six of seven HSP children, and in five of these six patients, abnormalities in the second portion of the duodenum were severe. They speculated that the duodenum was the main site of GI inflammation in HSP.…”
Section: Discussionmentioning
confidence: 97%